Desentralisasi, Tata Kelola Pemerintahan, dan Kemiskinan di Negara-Negara Berkembang - Sujarwoto, Sujarwoto (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
Theoretical arguments of the link between decentralisation, governance and poverty reduction are merit, but the implementation of decentralisation often fails to reduce poverty. This paper examines why decentralisation works and does not work to reduce poverty in developing countries. It shows that decentralisation will benefit for poverty alleviation if exist local political competition, community participation, and capacity of local government.